Evaluation and Selection of CO2-water Alternating Flooding Favorable Area Based on Flow-units Analysis. (July 2017) - Yu, Bowei; Zhang, Xiaoli; Du, Meixin; Ju, Yinjuan
Abstract: CO2 Enhance Oil Recovery (CO2 -EOR) not only can enhance oil recovery and prolong producing life of oil field, but also can seal a part of CO2 into the subsurface. It exerts positive effect on reducing CO2 -emission and mitigating global warming. This paper studied the influence factors on CO2 -water alternating flooding efficiency of Chang 6 reservoir Triassic Yanchang Formation in Qiaojiawa area, Ordos basin, through the CO2 -water alternating flooding experiment. In order to evaluate and select favorable area of CO2 -water alternating flooding, reservoir flow units are adopted to choose the permeable geologic unit with good interwell dynamical communications. Flow units are divided by gray correlation analysis method with key parameters including flow zone indicator ( FZI ), permeability, porosity, shale content and median grain diameter. It turns out that the reservoir is divided into three kinds of flow units marked as I, П and Ш. The permeability of type I flow unit is relatively better, which FZI ranges from 2.50 to 5.01, porosity ranges from 9.50% to 12.90%, permeability ranges from 0.86×10 -3  μm 2 to 2.79×10 -3  μm 2, shale content ranges from 9% to18%, median grain diameter ranges from 0.15 mm to 0.31 mm. The results of experiment suggest that CO2 -water alternating flooding efficiency ranges from 51.2% to 62.7%, the average is 58.7% which is 10.1% higher than that of water flooding. The efficiency of CO2 -EOR improves dramatically when the permeability of reservoir is relatively high, especially when the permeability is greater than 1.0×10 -3  μm 2 . The samples with permeability greater than 1.0×10 -3  μm 2 are just taken from type I flow unit. So, CO2 -water alternating flooding favorable area should be selected in type I flow unit based on the characteristics of type I flow unit, the results of experiment, and production performance.